Teachers’ and Students’ Support for Corporal Punishment—A Practice Outlawed by the Government of Kenya - Matofari, Fredrick N. (Journal of interpersonal violence, 2021)
Application of corporal punishment (CP) in Kenyan schools continues to be controversial in that CP is banned but esteemed by parents, some teachers, and even students. This investigation sought to establish and describe participants’ degrees of support for the application of CP in schools in Eldoret Municipality. Randomly selected samples of 86 teachers and 192 students were investigated for their support of CP through survey questionnaires. Data analysis was undertaken using nonparametric and descriptive statistics. Teacher support for CP was found to be undifferentiated by gender, teaching experience, and professional qualification. Teachers with less than 12 years of teaching experience were more pro-CP in attitude compared with their older colleagues. A higher ratio of male-to-female teachers is associated with a greater tendency to apply CP in the schools investigated. Differences in support for CP among students were found by gender, age, and school grade. The findings have implications for school discipline and success of the government ban.